Gulf Coast Tick, Amblyomma maculatum Koch (Acari: Ixodidae: Amblyomminae) - Jeffrey C. Hertz; Phillip E. Kaufman (EDIS, 2014)
Gulf Coast ticks are found in grass prairies and coastal uplands throughout much of the western hemisphere. The ticks are ectoparasites that feed on a variety of birds and mammals, and will readily bite humans. Gulf Coast ticks are of increasing concern because of their ability to transmit several pathogens of veterinary and medical importance. This 7-page fact sheet was written by Jeffrey C. Hertz and Phillip E. Kaufman, and published by the UF Department of Entomology and Nematology, October 2014. (Photo: Jeffrey C. Hertz, edited by Jane Medley)